2018
DOI: 10.1007/s11060-018-2790-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of prolonged survival for breast cancer patient groups with leptomeningeal metastasis (LM)

Abstract: The study aimed to assess factors affecting survival of breast cancer patients suffering leptomeningeal metastasis (LM) and to compare survivals in patients with LM as the first and only site of metastases at presentation to patients with LM and metastases in other organs, along with selecting a patient group which had the best survival outcomes. Subject groups consisted of 187 patients consecutively referred during 1999-2015. A Cox proportional hazards model was used to identify factors associated with prolon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
38
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 27 publications
5
38
1
Order By: Relevance
“…In fact, the only randomized clinical trial specifically designed to assess the role of IT chemotherapy in BC‐related LMD showed no benefit . Data from a recent retrospective series suggest that the association of systemic therapy and radiation therapy with better prognosis might be stronger than that of intrathecal therapy . These results are consistent with our data showing that both systemic treatment and radiotherapy associated with better outcome at univariate analysis in the overall population, whereas IT treatment did not.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, the only randomized clinical trial specifically designed to assess the role of IT chemotherapy in BC‐related LMD showed no benefit . Data from a recent retrospective series suggest that the association of systemic therapy and radiation therapy with better prognosis might be stronger than that of intrathecal therapy . These results are consistent with our data showing that both systemic treatment and radiotherapy associated with better outcome at univariate analysis in the overall population, whereas IT treatment did not.…”
Section: Discussionsupporting
confidence: 89%
“…Recently, molecularly targeted substances such as tyrosine kinase inhibitors (TKI) have produced encouraging results with proven activity in the CNS (41). In this context, primary histology and molecular analyses play an important role in recent data, since they decisively influence the range of available substances for systemic and LC treatment (33, 42, 43).…”
Section: Discussionmentioning
confidence: 99%
“…Estimated OS ranged from 10 to 17 weeks, and the application of ITC, as well as the combination with systemic chemo- or antihormonal therapy, was prognostic for a favorable outcome. On the other hand, high-grade histology, poor clinical performance and triple-negative tumors had a significant negative impact on survival (11, 43, 49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median over all survival (OS) of patients after LM dia gnosis does not exceed 6 months [3]. The factors associated with increased survival are Karnofsky performance score ≥ 70, age > 53, luminal bio logical subtype of BC (ER+ PR+ HER2-), systemic ther apy, intrathecal ther apy and RT [4].…”
Section: Discussionmentioning
confidence: 99%